(untitled) (Perioperaciina Medicina, 2022)
Treatment of acute paraproctitis remains an urgent surgical problem which is associated with both the choice of surgical tactics and the peculiarities of postoperative management of patients. The article presents a comparative analysis of postoperative treatment of 59 patients with acute paraproctitis without concomitant pathology and vascular lesions according to the generally accepted and improved methods using Rheosorbilact, Arginine hydrochloride, Pentoxifylline, Decametoxin. Schemes of treatment are described. The rate of postoperative wound healing was assessed by the time of granulation in the wound and the decrease in wound volume. It is established that the proposed scheme of drug treatment in the postoperative period reduces the duration of the first phase of the wound process by 25–30 %, and the average weekly rate of postoperative wound healing is higher compared to the control group by 12–15 %.